EMPOWERING ELEMENTRY SCHOOL TEACHERS THROUGH CREATIVE AND CONTEXTUAL PEDAGOGICAL STRATEGI MENTORING - Ayi Abdurahman; Setiawati Setiawati; Wulan Widaningsih; Wiwin Winarni; Kohar Pradesa; Sri Erwini Christine; Sajidin Sajidin (Universitas Pahlawan Tuanku Tambusai, 2025)
Elementary school teachers play a critical role in shaping the foundation of student learning, yet many still rely on traditional, non-contextual teaching methods that fail to meaningfully engage students. This community service initiative aims to empower elementary school teachers through a mentoring program that focuses on creative and contextual pedagogical strategies. Using a Participatory Action Research (PAR) approach, the program was implemented over a two-month period; April-May 2025 in two public elementary schools in Sukabumi, West Java. The program involved collaborative lesson planning, classroom-based mentoring, and reflective practice sessions. Data were collected through pre- and post-program surveys, interviews, and teacher journals, then analyzed using qualitative thematic analysis and Pearson correlation techniques. The results showed significant increases in teachers’ confidence, creativity, and contextual awareness in teaching, as well as increased student engagement. Teachers began to integrate local culture, materials, and everyday experiences into their teaching, creating a more relevant and participatory learning environment. The program’s mentoring model proved effective in fostering teacher agency and sustained pedagogical innovation. This initiative contributes to the model of teacher professional development by demonstrating how participatory and localized mentoring can bridge the gap between theory and practice in primary education.